2001
DOI: 10.1128/mmbr.65.2.288-318.2001
|View full text |Cite
|
Sign up to set email alerts
|

Natural Biology of Polyomavirus Middle T Antigen

Abstract: “It has been commented by someone that ‘polyoma’ is an adjective composed of a prefix and suffix, with no root between—a meatless linguistic sandwich” (C. J. Dawe). The very name “polyomavirus” is a vague mantel: a name given before our understanding of these viral agents was clear but implying a clear tumor life-style, as noted by the late C. J. Dawe. However, polyomavirus are not by nature tumor-inducing agents. Since it is the purpose of this review to consider the natural function of middle T antigen (MT),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 393 publications
(403 reference statements)
1
34
0
Order By: Relevance
“…3A). We then assayed the activation state of the Akt and Erk kinases, which are known to act downstream of PyMT-mediated signaling pathways (13). Western blot analysis showed that both Akt and Erk are more highly phosphorylated, and presumably more active, in tumors than in normal tissue (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3A). We then assayed the activation state of the Akt and Erk kinases, which are known to act downstream of PyMT-mediated signaling pathways (13). Western blot analysis showed that both Akt and Erk are more highly phosphorylated, and presumably more active, in tumors than in normal tissue (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The hydrophobic C-terminal region of PyMT required for its membrane binding (Gottlieb and Villarreal, 2001;Ichaso and Dilworth, 2001) is absent in both the PyMT8C and PyMT10C proteins. Thus it was of interest to determine the cellular location of these PyMT proteins in PyMT8C and PyMT10C cells.…”
Section: The Cellular Location Of the Pymt Mutant Proteinsmentioning
confidence: 99%
“…The loss of the ability of PyMT to bind to membranes is known to have an effect on transformation (Gottlieb and Villarreal, 2001;Ichaso and Dilworth, 2001) explaining the normal phenotype of REF52 cells containing the PyMT8C and PyMT10C mutant PyMT proteins. We find that the loss of the C-terminal PyMT region containing the hydrophobic region also affects the ability of PyMT to induce ARF.…”
Section: Pymt10c Retrovirusmentioning
confidence: 99%
See 1 more Smart Citation
“…The polyoma virus (Py) early region specifies three proteins, large T-antigen (PyLT), middle T-antigen (PyMT), and small T-antigen (PyST), by differential splicing of mRNA derived from the same genomic DNA sequence (1). The membrane-bound PyMT is a potent activating oncogene, which has no intrinsic enzyme activity but acts as a scaffolding protein and binds and modulates the activities of a number of important cellular signaling proteins (1,2). Studies with PyMT have provided great insight into a number of critical cellular signaling pathways involved in growth control (3).…”
mentioning
confidence: 99%